PERILAKU KONSUMTIF REMAJA DI WARUNG KOPI DI KOTA MUNTOK - Fizarya Ananda; Subandi Haris; Erwansyah (Melati Institute, 2023)
This study aims to determine the variety of consumptive behavior of teenagers in coffee shops. This research was conducted in Muntok City, West Bangka Regency. This research uses qualitative methods, with the type of case study research. The selection of subjects in the study was carried out using purposive sampling technique, which amounted to three groups. Data collection methods were carried out using interviews, observation, and documentation. The results showed that (1) Coffee shops are places where teenagers gather after school, (2) Coffee shops are places to share stories and play games on cellphones, (3) Coffee is proven to relieve stress after their activities at school. Translated with www.DeepL.com/Translator (free version)